Inaczej, tak samo? – Umieranie zwierząt - Borzymowska, Barbara (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Humans attitude toward animals death depends on their attitude towards living animals. Its characterized by either indifference up to cruelty or is treated similar to the death of human family members accompanied by the same kind of mourning. Religions are also characterized by big range of opinions of animals passing away – from indifference of catholics to similar attitude towards all kinds of live and its end of Buddhists or very specific ideas of terianthropics. Owners passing away can be deciding problem for animals who stay
Keywords: animals; dying; death; animals cemetery; mourning